The Role of Digital Communication in Improving the Efficiency of Plantation Management - Sinuhaji, Yose Andre (Persepsi: Communication Journal, 2024)
Plantation management in Indonesia plays an important role in supporting the national economic sector. Digital transformation has brought significant changes through the implementation of digital communications such as mobile applications, web-based systems, and cloud platforms. This technology speeds up workflows, improves data-driven decision-making, and facilitates coordination between stakeholders. This study uses a qualitative descriptive method to analyze the impact of digital communication in improving plantation operational efficiency. The results show that digitalization allows for more effective resource management, reduced operational costs, and increased productivity. However, there are challenges in the form of low digital literacy of field workers, limited internet infrastructure, and the need for technology training. In addition to supporting operational efficiency, digital technology also contributes to environmental sustainability by minimizing the use of excess chemicals. Successful digital transformation requires collaboration between governments, the private sector, and stakeholders to develop digital infrastructure, provide intensive training, and increase motivation for technology adoption. This research emphasizes that digitalization is a strategic step that not only strengthens the plantation sector but also supports economic and environmental sustainability in Indonesia.